REDD+ ÑUE JOOK+GA - ÑUE +DAZIGA2 (REDD+ well-woven or wellfitted) - Almonacid Márquez, Rafael R. (2025)
Opinion article The implementation of REDD+ projects is examined, emphasizing that indigenous peoples are the owners, highlighting the crucial integration of their traditional knowledge systems in all stages of the process. The projects aim to mitigate the potential effects of climate change by reducing emissions from deforestation and degradation, respecting their ancestral rights, wisdom, preserving biodiversity and ensuring environmental and social sustainability. It highlights the recognition by the Intergovernmental Panel on Climate Change (IPCC) of these knowledge systems in climate action, highlighting their dynamism, capacity to evolve and adapt, facilitating research and effective decision making. In addition, it illustrates how consent to the “good word” and respect for ancestral knowledge are essential for the success of these projects, through integrated territorial management that reflects a deep respect for indigenous narratives. Through the analysis of concrete cases, progress and challenges faced are explored. The results indicate that genuine and comprehensive engagement of indigenous communities can translate into lasting benefits for both the environment and the societies benefiting from REDD+ projects.